Luther - Mullett, Michael (Lancaster Pamphlets, 1986)
Luther provides a clear exposition of the state of German politics on the eve of the Reformation. Dr Mullett concentrates particularly on the evolution of Luther's thought and its central preoccupation with re-aligning the church's theology with that of the New Testament.